CORRECTION OF THE GENETIC EFFECT OF DALAPONA (HERBICIDE) WITH THE HELP OF PLANT EXTRACTS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2022)
In animals of the control group, the level of spontaneous mutation in the bone marrow and testis cells was very low. After a 3-month administration of dalapon in bone marrow cells, the number of chromosome aberrations (2.64%) and PChE with micronuclei (5.65%) increased by 5-6 times compared with the control ones (0.41 and 0.91%, respectively). The number of chromosome mutations increased by 7 times, and in spermatocyte cells - by 1.34%; the number of spermatozoa with abnormal heads increased by 9 times (3.70%) compared with the control (0.17 and 0.50%).